Complications and failures of secondary prevention in acute ischaemic stroke - Geraghty, O (2011)
Stroke is a leading cause of death and the most common cause of disability in adults in the United Kingdom. Several treatments are effective in preventing stroke in the long term after TIA and minor ischaemic stroke, including aspirin, other antiplatelet agents, and blood pressure lowering drugs, statins and anticoagulation in atrial fibrillation. However, failure of secondary prevention to prevent recurrent vascular events is still a major clinical problem, as is the risk of bleeding associated with antiplatelet agents and anticoagulants. This thesis determines the risks associated with urgent secondary prevention in the acute phase after TIA and minor stroke, particularly the reduction in risk of early recurrent stroke, the risk of bleeding with combination of aspirin and clopidogrel in the acute phase and whether or not there is a rebound increase risk of ischaemic stroke or recurrent TIA after withdrawal of a short course of clopidogrel. I have shown that urgent and early treatment of ischaemic stroke with secondary prevention leads to an 80% reduction in recurrent stroke. I have also shown that an increased bleeding risk exists among aspirin naïve patients treated with combination antiplatelet medications compared to those already treated with aspirin. My work has also shown that discontinuation of clopidogrel following treatment for 30 days or more does not lead to a rebound increase in ischaemic stroke. Bleeding events are a frequent complication of antiplatelet treatment in TIA and ischaemic stroke. I have shown that the long term risk of bleeding in a population study treated with antiplatelets is 6% per 100 person years. Using this information I identified risk factors for bleeding to develop a clinical baseline bleeding model to identify those at higher risk of bleeding. Age was identified as a significnant risk factor for both bleeding and recurrent ischaemic risk. In addition, bleeding events are associated with higher rates of fatality and disability in the older population. Finally, I have shown that the time trends in stroke recurrence differ depending on the presenting event i.e TIA or stroke. Stroke recurrence risk after minor stroke is delayed compared with TIA, and remains high during the late phase despite current best medical treatment. Blood pressure control and atrial fibrillation are risk factors for late stroke recurrence identifying the unmet need for better detection and treatment potentials to reduce late recurrent stroke.